1993
DOI: 10.1111/j.1365-2044.1993.tb07074.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe bronchospasm during epidural anaesthesia

Abstract: SummaryA case of severe bronchospasm occurring during epidural anaesthesia in a patient undergoing Caesarean section is described. The aetiology of the bronchospasm may have been related to sympathetic nervous blockade allowing unopposed parasympathetically mediated bronchoconstriction. Key wordsAnaesthetic techniques, regionae epidural. Complications; bronchospasm.Bronchospasm during anaesthesia is an undesirable, and sometimes serious, complication; it may be so intense that oxygenation of the patient become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 6 publications
0
5
1
2
Order By: Relevance
“…4) blockade on airway resistance are not well understood. It is generally believed that the development of severe bronchoconstriction during epidural anaesthesia is due to a blockade of the innervating sympathetic nerve to the lungs and/or a decrease in circulating adrenaline (1)(2)(3). This contrasts with our findings which demonstrated that the blockade of neural sympathetic outflow by epidural anaesthesia was not relevant to peripheral airway resistance, neither at rest nor during a bronchoconstrictive challenge in dogs.…”
Section: Discussioncontrasting
confidence: 99%
“…4) blockade on airway resistance are not well understood. It is generally believed that the development of severe bronchoconstriction during epidural anaesthesia is due to a blockade of the innervating sympathetic nerve to the lungs and/or a decrease in circulating adrenaline (1)(2)(3). This contrasts with our findings which demonstrated that the blockade of neural sympathetic outflow by epidural anaesthesia was not relevant to peripheral airway resistance, neither at rest nor during a bronchoconstrictive challenge in dogs.…”
Section: Discussioncontrasting
confidence: 99%
“…Patients were not studied if they had ingested aspirin within the preceding 10 days, if they were receiving heparin or warfarin or if coagulation study results were outside the normal range. Obese patients (body mass index >30 kg.m -2 ) and those with neurological disease, poor left ventricular function (ejection fraction <40%) or reversible airways obstruction (which can be exacerbated by the use of high epidural blockade [9]) were also not studied. Baseline pre-operative respiratory function was determined the evening before surgery by respiratory spirometry (forced expired volume in 1 s: FEV 1 , forced vital capacity: FVC) and peak expiratory flow (PEF).…”
Section: Methodsmentioning
confidence: 99%
“…El propofol se considera es el agente de elección para la inducción de la anestesia en los asmáticos (39) , y la ketamina también tiene propiedades broncodilatadoras (40) . El uso de la anestesia regional no reduce las complicaciones postoperatorias pulmonares en asmáticos asintomáticos, mientras que es ventajoso en pacientes sintomáticos (41) . La terapia debe ser dirigida hacia la optimización de la oxigenación y el diagnóstico apropiado necesita ser establecido, dado que "no todo lo que sibila es asma".…”
Section: Factores De Riesgo De Complicaciones Postoperatorias Pulmonaresunclassified